2023
DOI: 10.1155/2023/4835839
|View full text |Cite
|
Sign up to set email alerts
|

MiR-100 rs1834306 A>G Increases Biliary Atresia Risk in Southern Han Chinese Children

Abstract: Background. Biliary atresia (BA) is a type of severe cholestatic childhood disease that may have a genetic component. miR-100 plays a key role in regulating cell apoptosis, proliferation, and inflammatory reactions. A single-nucleotide polymorphism in miR-100 has been proven to modulate susceptibility to various diseases. Methods. We conducted a case-control retrospective study to explore the correlation between miR-100 gene polymorphism (rs1834306 A>G) and biliary atresia susceptibility in 484 Chinese pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Zhu et al 48 reported that the miR‐100 rs1834306 A > G polymorphism is associated with enhanced risk of Hirschsprung disease in children in southern China. Recently, Chang et al 49 discovered that the miR‐100 rs1834306 A > G polymorphism might also increase predisposition to biliary atresia in Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al 48 reported that the miR‐100 rs1834306 A > G polymorphism is associated with enhanced risk of Hirschsprung disease in children in southern China. Recently, Chang et al 49 discovered that the miR‐100 rs1834306 A > G polymorphism might also increase predisposition to biliary atresia in Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in microRNAs have been reported to affect the development and prognosis of various diseases. In particular, polymorphisms in microRNA-100 (rs1834306 A>G), microRNA-499 (rs3746444 A>G), microRNA-492 (rs2289030 G>C) and microRNA-938 (rs2505901 T>C) may contribute to BA susceptibility (95)(96)(97).…”
Section: Micrornas In Liver Diseasesmentioning
confidence: 99%